2010
DOI: 10.1007/978-1-60761-762-4_14
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Membrane Protein Structures Using Solution and Solid-State NMR

Abstract: NMR is an essential tool to characterize the structure, dynamics, and interactions of biomolecules at an atomic level. Its application to membrane protein (MP) structure determination is challenging and currently an active and rapidly developing field. Main difficulties are the low sensitivity of the technique, the size limitation, and the intrinsic motional properties of the system under investigation. Solution and solid-state NMR (ssNMR) have common and own specific requirements. Solution NMR requires a care… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…The relative percent yields of the three most important products obtained by chemical trapping with each of these nucleophiles were renormalized and are listed in Table 2. 16-ArN 2 + also reacts with primary and secondary amide 43 The percentage yields substituted into the normalized yields equation can be found in Tables S3b-1, S3b-2, S3c-1, and S3c-2 of the Supporting Information. nitrogens (SLG), and observable products are not formed from tertiary amides such as the amide nitrogen on SLS.…”
Section: ■ Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The relative percent yields of the three most important products obtained by chemical trapping with each of these nucleophiles were renormalized and are listed in Table 2. 16-ArN 2 + also reacts with primary and secondary amide 43 The percentage yields substituted into the normalized yields equation can be found in Tables S3b-1, S3b-2, S3c-1, and S3c-2 of the Supporting Information. nitrogens (SLG), and observable products are not formed from tertiary amides such as the amide nitrogen on SLS.…”
Section: ■ Resultsmentioning
confidence: 99%
“…For example, X-ray crystallography (XRC) provides detailed information on the structures of membrane proteins; ,, however, the crystals are located not within a membrane bilayer, but in protein–detergent complexes. ,, Nuclear magnetic resonance (NMR) spectroscopy provides information on the entire protein structure and potentially the surrounding bilayer lipids. , The polarity of the local environment can be obtained from Hα, 13 Cα, and HN nuclei and also from water–amide exchange measurements . However, high-resolution spectra require substantial protein concentrations, , and both size limits ,, and line broadening can be a problem. Circular dichroism (CD) reports the fractions of the protein in its secondary conformations, infrared spectroscopy (IR) provides information on the secondary structure of the protein by detecting the change of the hydrogen-bonding interactions of amide groups within the proteins, , and both methods provided information on protein orientation in vesicles .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…43,44 Differentiated mesenchymal stem cells synthesize and secrete neurotrophins. 45 Similarly, it has been reported that differentiated mesenchymal stem cells have the potential to infl uence the expression of growth factors and myelination of axons in different levels.4 6,47 However, Wang et al, 2009, reports that bone marrow induced stem cells increase peripheral nerve regeneration not only by secreting neurotrophic factors, but also indirectly by affecting Schwann cell proliferation rate. 36 Although bone marrow stem cells are more easily obtained when compared with embryonic stem cells, their proliferation capacity is less when compared with embryonic stem cells.…”
Section: Bone Marrow Derived Stem Cellsmentioning
confidence: 99%
“…Since ClC-ec1 is an alpha helical dimer of 50 kD per subunit, we aimed not to attempt the heroic feat of full NMR solution-state structure determination (Montaville and Jamin 2010), but rather to employ sparse labeling strategies that would minimize signal overlap, facilitate peak assignment and allow us to identify additional regions of conformational change. We targeted 13 C-methyl groups because the intrinsic sensitivity of three protons coupled to one carbon together with favorable relaxation properties make them well suited to the solution-state study of high-molecular-weight systems (Beatty et al 1996; Butterfoss et al 2010; DellaVecchia et al 2007; Mainz et al 2013; Religa et al 2011), including membrane proteins, where size is exacerbated by the surrounding detergent micelle or lipid bicelle (Kang and Li 2011; Kim et al 2009; Sanders and Sonnichsen 2006).…”
Section: Introductionmentioning
confidence: 99%